Does public R&D complement or crowd-out private R&D in pre and post economic crisis of 2008? - Naqeeb-ur-Rehman; Eglantina Hysa; Xuxin Mao (Journal of Applied Economics, 2020)
Research and development expenditure (R&D) generate innovation and contribute significantly to the economic development. Previous studies emphasized the role of public R&D to encourage the technological innovation in the private sector. However, the effect of global economic crisis with respect to the public and private R&D link has been somewhat neglected in the empirical literature. Based on system GMM estimation, we found that public R&D complements private R&D in pre and post economic crisis. However, the strength of their complementary association is found strong in pre-economic crisis. In sum, the results indicate that continuous support to public R&D in pre and post economic crisis accelerate the technological innovation in the private sector. This study implies that public support to R&D is a good strategy for an economy to confront economic crisis effectively by increasing the technological innovation in the private sector. For policy makers, it is suggested that care must be taken while investing in the R&D, the investment is to be based on the ratio between R&D expenditure to number of R&D workers.
Keywords: 330; economic crisis; innovation; R&D